Mass movement risk in a Portuguese municipality: Tabuaço case study. Issue 3 (15th February 2021) - Rodrigues, André; Reis, Johnny; Pinto, Filipe; Lucas, Davi
Abstract : In the past century, Portugal was affected by several natural disasters, such as mass movements, which often caused high levels of destruction. However, data on past events related to mass movements were scattered. Mass movements are one of the most relevant geomorphological hazards in Portugal, by the high levels of people affected, destruction of assets and disruption of economic and social activities. The main objective of this study was to identify the risk of mass movements in the municipality of Tabuaço, integrated in an important Oporto wine production area, the Douro Wine Region, using geographic information systems. The results show the main areas susceptible to this type of risk, according to a realistic and practical methodology resulting from a deep knowledge of the terrain. This study can prove to be a powerful tool for adaptation and mitigation by civil protection authorities and for the creation of new policies for municipal and spatial planning, to support decision makers.